The Role of Dietary Phenolic Compounds in Epigenetic Modulation Involved in Inflammatory Processes - Milan Číž; Adéla Dvořáková; Veronika Skočková; Lukáš Kubala (MDPI AG, 2020)
A better understanding of the interactions between dietary phenolic compounds and the epigenetics of inflammation may impact pathological conditions and their treatment. Phenolic compounds are well-known for their antioxidant, anti-inflammatory, anti-angiogenic, and anti-cancer properties, with potential benefits in the treatment of various human diseases. Emerging studies bring evidence that nutrition may play an essential role in immune system modulation also by altering gene expression. This review discusses epigenetic mechanisms such as DNA methylation, post-translational histone modification, and non-coding microRNA activity that regulate the gene expression of molecules involved in inflammatory processes. Special attention is paid to the molecular basis of NF-κB modulation by dietary phenolic compounds. The regulation of histone acetyltransferase and histone deacetylase activity, which all influence NF-κB signaling, seems to be a crucial mechanism of the epigenetic control of inflammation by phenolic compounds. Moreover, chronic inflammatory processes are reported to be closely connected to the major stages of carcinogenesis and other non-communicable diseases. Therefore, dietary phenolic compounds-targeted epigenetics is becoming an attractive approach for disease prevention and intervention.